REVIEW STUDI KONFIGURASI KEADILAN ORGANISASIONAL DAN MODAL SOSIAL - Yuli Arisanti (LPSDI Bina Patria, 2023)
This study is a review of the article Configuration of organizational justice and social capital: their impact on satisfaction and commitment, published in the International Journal of Business Excellence journal, Vol. 17, No.3, 2019. This study argues that the limited information of individuals in responding to organizational policies forces them to judge fairness subjectively. Using an experimental design, this study addresses the controversy over the impact of distributive and procedural justice on job satisfaction and organizational commitment. Some critics for Tjahjono were the importance to mention the negative side of social capital for more balancing view on social capital, and the suggestion to do experiment on regular working staff in organizations instead of junior university students. Overall the article has shown comprehensive empirical study In The Subject Of Satisfaction And Organisational Commitment.